Experimental organic chemistry : a small-scale approach - Wilcox, Jr., Charles F.; Wilcox, Mary F. (Englewood Cliffs, New Jersey : Prentice-Hall, 1995)
Takes a small scale approach to experimentation, keeping costs of material and their disposal down by a factor of five coompared to standard scale, while retaining most standard scale equipment and requiring no special glassware.
Introduction -- Separation and purification of organic compounds -- Identification of organic compounds -- Preparation and reactions of typical organic compounds -- Compounds of medicinal and biological interest.
Includes index.
Keywords: CHEMISTRY, ORGANIC -- LABORATORY MANUALS